Efficient clofilium tosylate-mediated rescue of POLG-related disease phenotypes in zebrafish - Nicola Facchinello (Cell Death and Disease, 2021)
Abstract The DNA polymerase gamma (Polg) is a nuclear-encoded enzyme involved in DNA replication in animal mitochondria. In humans, mutations in the POLG gene underlie a set of mitochondrial diseases characterized by mitochondrial DNA (mtDNA) depletion or deletion and multiorgan defects, named POLG disorders, for which an effective therapy is still needed. By applying antisense strategies, ENU- and CRISPR/Cas9-based mutagenesis, we have generated embryonic, larval-lethal and adult-viable zebrafish Polg models. Morphological and functional characterizations detected a set of phenotypes remarkably associated to POLG disorders, including cardiac, skeletal muscle, hepatic and gonadal defects, as well as mitochondrial dysfunctions and, notably, a perturbed mitochondria-to-nucleus retrograde signaling (CREB and Hypoxia pathways). Next, taking advantage of preliminary evidence on the candidate molecule Clofilium tosylate (CLO), we tested CLO toxicity and then its efficacy in our zebrafish lines. Interestingly, at well tolerated doses, the CLO drug could successfully rescue mtDNA and Complex I respiratory activity to normal levels, even in mutant phenotypes worsened by treatment with Ethidium Bromide. In addition, the CLO drug could efficiently restore cardio-skeletal parameters and mitochondrial mass back to normal values. Altogether, these evidences point to zebrafish as a valuable vertebrate organism to faithfully phenocopy multiple defects detected in POLG patients. Moreover, this model represents an excellent platform to screen, at the whole-animal level, candidate molecules with therapeutic effects in POLG disorders.